Best Answer

9 plus 7 equals 144.

The series is formed by multiplying the first number with the sum of both numbers.

2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

Q: If 2 plus 3 equals 10 and 7 plus 2 equals 63 and 6 plus 5 equals 66 and 8 plus 4 equals 96 then what does 9 plus 7 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

144, you add the plus numbers, then multiply it by the first.

144, you add the plus numbers, then multiply it by the first.

This or a similar question has already been answered. 2_plus_3_equals_10_7_plus_2_equals_63_6_plus_5_equals_66_8_plus_4_equals_96_then_9_plus_7_equals_what144.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

273 13+8 = 21 and 13*21 = 273

Related questions

26

96

144

144

144 add the two numbers and multiply by the first 2(2 + 3) = 10 7(7 + 2) = 63 etc.

If I am correct, 9 plus 7 equals 112.

144, you add the plus numbers, then multiply it by the first.

144, you add the plus numbers, then multiply it by the first.

This or a similar question has already been answered. 2_plus_3_equals_10_7_plus_2_equals_63_6_plus_5_equals_66_8_plus_4_equals_96_then_9_plus_7_equals_what144.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

144 9+7 = 16 and 9*16 = 144